Leveraging foreign institutional logic in the adoption of stock option pay among J apanese firms - Geng, Xuesong; Yoshikawa, Toru; Colpan, Asli M. (Strategic Management Journal, 2016)
Research summary : We investigate why J apanese firms have adopted executive stock option pay, which was developed with shareholder‐oriented institutional logic that was inconsistent with J apanese stakeholder‐oriented institutional logic. We argue that J apanese managers have self‐serving incentives to leverage stock ownership of foreign investors and their associated institutional logic to legitimize the adoption of stock option pay. Our empirical analyses with a large sample of J apanese firms between 1997 and 2007 show that when managers have elite education, high pay inequality with ordinary employees, and when firms experience poor sales growth, foreign ownership is more likely associated with the adoption of stock option pay. The study shows the active role of managers in facilitating the diffusion of a new governance practice embodying new institutional logic . Managerial summary : Why have J apanese firms adopted stock option pay for executives? Inconsistent with J apanese stakeholder‐oriented tradition in corporate governance, such pay has been believed to prioritize managerial attention to the interests of shareholders over those of other stakeholders. However, to the extent that shareholders' interests are legitimate in the J apanese context, executives who have self‐serving incentives to adopt such pay can leverage the need to look after shareholders' interest in their firms to legitimize their decisions. In a large sample of J apanese firms, we find that foreign ownership (representing shareholders' interests) is more likely to be associated with the adoption of stock option pay when managers are motivated to receive such pay, such as when they have elite education, high pay inequality with ordinary employees, or poor sales growth . Copyright © 2015 John Wiley & Sons, Ltd.